Fox & Rabbit. 2, Make believe - Ferry, Beth (Amulet Books, 2020)
"Fox and Rabbit are the very best of friends. They do everything together. Good things like getting ice cream and not-so-good things like getting bad haircuts. But when they meet a new friend, Owl, Fox isn't so sure if there's enough friendship to go around. They have lots of fun exploring the depths of Owl's big imagination. Together, Fox and Rabbit and Owl sail the high seas, get swallowed by a whale, defeat evil woodchucks, and more- all from the comfort of the playground."--Provided by publisher.